Kemampuan Peserta Didik Menggunakan Kata Penghubung dalam Karangan Deskripsi pada Tema 1 Subtema 2 Pb 2 Kelas V SD Negeri 40 Banda Aceh - Ratnasari, Devi; Nurhaidah, Nurhaidah; Yamin, M. (Elementary Education Research, 2023)
This research is entitled "Students' Ability to Use Connecting Words in Writing Descriptions on Theme 1 Sub-theme 2 Pb 2 Class V SD Negeri 40 Banda Aceh". As for the formulation of the problem in this study, how is the ability of students to use connecting words in descriptive essays on Theme 1 Sub-theme 2 Pb 2 Class V SD Negeri 40 Banda Aceh? This study aims to describe the ability of students to use conjunctions in descriptive essays on Theme 1 Sub-theme 2 Pb 2 Class V SD Negeri 40 Banda Aceh. This study uses a qualitative approach and the type of descriptive research. The subjects in this study were all fifth-grade students of SD Negeri 40 Banda Aceh, totaling 34 students. The data collection technique used a written test in the form of questions or contents in the form of discourse. The results showed that there were 15 students who scored in the "very capable" category. students with the category of "able" as many as 7 people. As well as students who "notable" as many as 12 people. The average value of students' ability to use connecting words in descriptive essays on Theme 1 Sub-theme 2 PB 2 Class V SD Negeri 40 Banda Aceh is 83.38 or is in the capable category. This is in accordance with the following conditions: 89 A 100 (very capable), 79 B 89 (able), and 70 C 79 (not yet capable). So it can be concluded that the ability of students to use connecting words in descriptive essays on Theme 1 Sub-theme 2 PB 2 Class V SD Negeri 40 Banda Aceh is categorized as capable.